Evaluation of Sealing Ability of AH Plus And TG Root Canal Sealers in the Presence and Absence of Smear Layer - Tahir Ali Khan; Nighat Shafique; Mumtaz -; Raham Zaman (Gandhara University, 2015)
Background: Smear layer is considered to be the main contributing factor in better sealing and adhesion of a sealer. Objective: The aim of this study is to determine the sealing ability of two root canal sealers (AH Plus and tg). In the presence and absence of smear layer Methodology: Extracted teeth from patients visiting Sardar Begum Dental College 60 in numbers were used in this study. Specimens were divided in to two main groups (group1 and group 2) both groups were instrumented using a step back technique. Irrigation was done during instrumentation with one ml of 5.25% NaOCl solution. In group2 a final flush with 10 ml of 17% EDTA solution followed by 10ml of 5.25% NaOCl was used for smear layer removal. Each group then further divided in to two sub groups (n=15). After obturation specimens were kept in separate containers with wet gauze to maintain 100% humidity. The specimens were coated with nail polish except for apical 2mm. Specimens were then suspended vertically in two % methylene blue dye for 7 days. Longitudinal sectioning was done to determine the extent of dye penetration using a stereo microscope at X30 magnification. Student t test was used for statistical analysis (p≤ 0.05). Results: The results showed that in the presence of smear layer, mean apical dye leakage of AH Plus was2.89 mm and tg was 4.02 mm. While in the absence of smear layer the mean dye leakage of AH Plus was 2.23 mm and tg was 3.28 mm. Student t test was more than p value indicating non significant result for both sealers. Conclusion: Apical sealing ability of AH Plus is better than tg root canal sealer in the presence and absence of smear layer.